Emerging Leadership Through Coloring: Stories of the Indiana Women of Achievement - Michelle Glowacki-Dudka; Amy L Baize-Ward EdD (Adult Education Research Conference, 2019)
Engaging adults in learning can occur through arts-based methods. Building on an oral-history project, we tell women’s leadership stories through both narrative and images through an adult coloring book.
Keywords: arts-based learning; leadership; women; coloring book